Langue-frontière ou langue-franche : L’hétérolinguisme dans la prose afropéenne et cubano-américaine - Ferdulis Zita Odome Angone (Carnets)
Our analysis is a cross-sectional study with a special focus on heterolinguism as language facts and effects in Leonora Miano and Cristina García’s works. We want to highlight the aporias that are observable in hybrid (or in-between) literatures; where translation plays a pivotal role. In Miano’s Francophone work, we will study the notions of African orality through storytelling. As for the Cuban American and English speaker Cristina García, we will discuss on Spanglish (or Espanglish or Espanglés) driving our analysis from the Cuban Santería. The subject here aims at highlighting this literature produced by minorities, with a specific focus on two main authors: Léonora Miano (from African European origins) and Cristina García (a Cuban American). In a time of heterotopic references, our theoretical approach will be multidisciplinary; for a fragmented or hybrid text (a heterogeneous text with multiple ancestralities) requires a plural look to better appreciate the polysemy of the mixed-identity soul within frontiers authors.